2012
DOI: 10.1016/j.ygcen.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Food conditions affect yolk testosterone deposition but not incubation attendance

Abstract: In many bird species with hatching asynchrony, yolk androgens increase across the laying sequence. This has been hypothesized to represent a compensatory mechanism for disadvantages of later-hatching chicks - via positive effects of yolk androgens on early competitiveness and growth. However, the costs and benefits of this compensatory strategy probably depend on environmental factors determining the survival chances of the chicks such as the food conditions, which should, therefore, influence maternal yolk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…In zebra finches under poor quality diet pre‐laying, yolk androgen levels decreased over laying sequence whereas there was a flat pattern under high quality diet (Sandell et al ). In canaries Serinus canaria , birds under poor quality diet showed less within‐clutch increase of androgen concentrations compared to good quality diet (Vergauwen et al ). Although the literature indicates that at least some bird species have short‐term flexibility of yolk androgen allocation to environmental factors (see also Kingma et al ), the potential differences in reaction to different environmental cues and among different species remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In zebra finches under poor quality diet pre‐laying, yolk androgen levels decreased over laying sequence whereas there was a flat pattern under high quality diet (Sandell et al ). In canaries Serinus canaria , birds under poor quality diet showed less within‐clutch increase of androgen concentrations compared to good quality diet (Vergauwen et al ). Although the literature indicates that at least some bird species have short‐term flexibility of yolk androgen allocation to environmental factors (see also Kingma et al ), the potential differences in reaction to different environmental cues and among different species remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the effect of yolk androgens on offspring may be dependent on environmental conditions (Groothuis et al , Müller et al , Tschirren et al ): females are expected to adjust deposition of maternal hormones in their eggs depending on prevailing environmental conditions or their own condition when these conditions are predictive for the conditions during offspring development, in order to adjust offspring phenotype to these conditions (predictive adaptive response, Lack ). Indeed, food supplementation before and during laying can affect yolk androgen levels but again the results are mixed, with some studies finding lower yolk androgen levels and/or an effect on the within clutch pattern (Verboven et al , Gasparini et al , Sandell et al , Vergauwen et al ), and others no effect (Verboven et al , Benowitz‐Fredericks et al ). Lower yolk androgen levels under good rearing conditions have been interpreted as to enable the chick to better bear the potential costs of androgens such as higher immunosuppression and oxidative damage whereas the stimulating effect of the hormone on begging behavior would be less important under such conditions (Verboven et al , Groothuis et al ).…”
mentioning
confidence: 99%
“…All of these factors have been shown to influence yolk hormones. For example, high quality food increased yolk testosterone (Vergauwen et al, 2012); in Great tits (Parus major), experimentally increased predation risk resulted in lower yolk testosterone (Coslovsky et al, 2012), and yolk testosterone was lower when females were exposed to nidicolous hen fleas (Heylen et al, 2012) and in nests with high ectoparasite loads (Tschirren et al, 2004). A significant higher load of red fowl mites (Dermanyssus gallinae) in the second year of our study (data not shown) could have been a cause of the lower yolk testosterone levels in that year.…”
Section: Discussionmentioning
confidence: 99%
“…2003; Vergauwen et al. 2012). In line with this, difference in yolk testosterone levels between the second and the first egg of black‐legged kittiwakes ( Rissa tridactyla ) has been reported to be larger (i.e., higher levels in second as compared to first‐laid egg) when food availability was intermediate than when it was low or high (Benowitz‐Fredericks et al.…”
Section: Introductionmentioning
confidence: 99%